Chemical Constituents from Sambucus adnata and Their Protein-Tyrosine Phosphatase 1B Inhibitory Activities - Tatsunori SASAKIa; Wei LIa; Haruna MORIMURAa; Songpei LIa; Qin LIb; Yoshihisa ASADAc; Kazuo KOIKEa (Chemical & Pharmaceutical Bulletin, 2011)
The MeOH extract from the whole plants of Sambucus adnata has shown significant protein-tyrosine phosphatase 1B (PTP1B) inhibitory activity. Chemical study on the extract resulted in the isolation of thirteen compounds, including a novel triterpene (1). The structure of 1 was determined to be 1α,3β-dihydroxy-urs-12-en-11-one-3-yl palmitate on the basis of extensive spectroscopic analyses. Among the isolated compounds, ursolic acid, oleanolic acid and (±)-boehmenan showed the most potent PTP1B inhibitory activity in vitro with the IC50 values of 4.1, 14.4 and 43.5 μm, respectively. The kinetic analysis indicated that (±)-boehmenan inhibits PTP1B activity in a competitive manner. Type-2 diabetes mellitus (T2DM) is a chronic metabolic disorder characterized by β-cell dysfunction and insulin resistance, and its prevalence has reached epidemic proportions worldwide. 1-3) Protein-tyrosine phosphatase 1B (PTP1B) is a major non-transmembrane phosphotyrosine phosphatase expressing ubiquitously in the classical insulin-targeted tissues4, 5) and functions as a negative regulator of the insulin-signaling pathway. 6, 7)